Konten Tiktok dalam mengkonstruksi pendidikan matematika di era digital - Nursirot, Mohammad Arul Sholehuddin; Khumainah, Nanda Dila Zahrotul (Maliki Interdisciplinary Journal, 2024)
The increasingly rapid development of technology means that news or information can not only be obtained from print media, but also from social media. One of the social media platforms that is currently viral among millennial teenagers is the Tiktok application. Based on data from We Are Social in the first quarter of 2022, Indonesia is in second place after the United States with 99.1 million active Tiktok users. In its development, Tiktok has also been used as an interesting and dynamic teaching tool for students, one of which is in learning mathematics. The use of TikTok as a learning medium has influenced efforts to construct mathematics education in this digital era if it is used as well as possible. This mathematics learning TikTok content is the first step in making the TikTok algorithm positive. So it is hoped that many TikTok content creators will fill their content with positive things that will dominate other content.